Electrochemical Sensors - Bakker, Eric; Qin, Y. (American Chemical Society, 2006)
This review gives an overview of electrochemical sensor research for the calendar years 2004 and 2005. References were collected by topic and author searches using databases such as ACS SciFinder. Since searches with sensor-related keywords are normally not as meaningful because of the vast use of the term sensor in the chemical sciences, we also manually skimmed through tables of contents of journals to identify key publications. Unfortunately, the limit of 200 references made it impossible to comprehensively cover the entire field of electrochemical sensors. Instead, emphasis was on fundamental advances of sensing principles, materials and characteristics. Only original and review articles published in widely available journals written in English were considered. Patents, book chapters, or book serials were omitted for this review. Applications, including electronic tongues and noses, are not covered here either to give more room for fundamental advances. Today, electrochemical sensors are tightly integrated and hyphenated with sampling, fluidic handling, separation, and other detection principles. Unfortunately, this review does not has sufficient room to cover these topics, and a reader should keep in mind that the topic of electrochemical sensors is relatively mature and has found its way into commercial products and advanced integrated sensing systems. Again, the focus here was on the reporting of fundamental advances, not so much on fabrication, integration, and hyphenation. As in past years, we have organized this review by topic, in the order of potentiometric, voltammetric, and gas sensors as well as reference electrodes that generally avoid the use of biological recognition elements, followed by electrochemical biosensors including affinity sensing principles. It should be emphasized that many such biosensors are not sensors in the strict sense, as their response behavior is often not reversible. Please keep in mind that this is a subjective collection of publications. Given the rather vast and active field of electrochemical sensor research, it is inevitable that this review gives an incomplete account of the status of the field. The authors apologize in advance for any possible oversights of important contributions, as they are bound to have occurred. Nonetheless, it should give the reader a snapshot of current activity in this important field and hopefully will provide motivation for further work on the understanding and development of chemical sensors.